Transformative Learning Management as A Learning Solution in MIS Islamiyah Muhammadiyah Walikukun Ngawi - Susilo Surahman (AL-ISHLAH: Jurnal Pendidikan, 2023)
Transformative learning is a form of education directed at achieving the search for solutions to problems that occur.  Consequently, learning should be based on a critical attitude towards the self and environment of the learners.  Transformative learning makes everyone involved in education aware that learning brings action and reflects effort. This study aims to explain transformative learning management in MIS Islamiyah Muhammadiyah Walikukun Ngawi. This research is field research.  Data analysis is done using the triangulation method by sorting, grouping, and concluding.  The results showed that self-transformation is a fundamental concept of learning applied in MIS Islamiyah Muhammadiyah Walikukun.  This basic foundation encourages schools to change the learning process's structure, characteristics, and substance.  In this case, the educator's function is a facilitator in providing a stimulus for changes in the attitudes and behavior of students in facing and solving problems that exist in themselves and their environment.